Endothelial tight junctions: permeable barriers of the vessel wall - Bazzoni, Gianfranco (Thrombosis and Haemostasis, 2006)
The endothelial lining of the vessel wall is a permeable barrier, which is located at the interface between the vascular and the perivascular compartments. Although the endothelium acts as an efficient barrier that strictly separates the two compartments,it may also act as a permeable filter which allows selective exchange of solutes and water between the luminal and abluminal sides of the barrier. Similarly to epithelia, also in the endothelium permeability follows two distinct routes, which have been termed transcellular pathway (across the apical and basolateral membranes of individual cells) and paracellular pathway (through the intercellular junctions and the lateral spaces between contacting cells). After an initial description of the two pathways, the review focuses on the cellular and molecular basis of the paracellular pathway, with emphasis on the role of intercellular tight junctions and tight junction-associated claudins. Finally, the signaling events that regulate paracellular permeability are discussed.
Keywords: Endothelial cells; permeability; tight junctions; ion channels